2022
DOI: 10.3389/fendo.2022.917794
|View full text |Cite
|
Sign up to set email alerts
|

Can Cervical Lymph Node Metastasis Increase the Risk of Distant Metastasis in Papillary Thyroid Carcinoma?

Abstract: BackgroundDistant metastasis (DM) is a rare event and has a negative effect on the prognosis for papillary thyroid carcinoma (PTC). The relationship between cervical lymph node metastasis and DM is complicated and unclear. This study aimed to evaluate the impact of N stage subclassification on different distant metastasis sites based on age stratification, especially for patients with papillary thyroid microcarcinoma.MethodsA total of 28,712 patient with PTC cases between 2010 and 2018 were extracted from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Papillary thyroid carcinoma (PTC) develops slowly, without causing obvious pain during the course of development, and it has a low rate of distant metastasis and death, so many potential patients are only identified postmortem [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) develops slowly, without causing obvious pain during the course of development, and it has a low rate of distant metastasis and death, so many potential patients are only identified postmortem [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, T1 stage (17,175,63.6%), N0 stage (20,567, 76.2%), M0 stage (26,735, 99.0%), TNM I stage (21,072, 78.1%), and localized (19,039, 70.5%) were more common. Papillary (18,400 , 68 .2%) was the most common pathological subtype, followed by papillary with follicular variant (7,405,27.4%) and FTC (1,193, 4.4%). A percentage of 98.4% patients had undergone thyroidectomy.…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…DTC has a favorable prognosis, with a 10-year overall survival rate exceeding 90% ( 5 ). Nevertheless, a small number of DTC patients present with distant metastasis (DM) at initial diagnosis, which is the leading cause of thyroid cancer-related mortality ( 6 , 7 ). The risk factors for DM have been widely discussed in previous studies, but the results were inconsistent in patients with DTC.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Researchers like Feng et al [8] have posited that distinctions may exist between PTC and PTMC, which is supported by studies demonstrating differences between PTC and PTMC concerning lymph node metastasis in the central area. [9] Given that preoperative evaluation are commonly done with noninvasive ultrasound, the presence of cervical lymph node metastasis (CLNM) is harder to determine due to being more concealed anatomically. This brings significance to findings by Feng et al [10] that suggested PTC has a stronger tendency of lymph node metastasis (CLNM) in the central region.…”
Section: Introductionmentioning
confidence: 99%